Romancing the difference : Kenneth Burke, Bob Jones University, and the rhetoric of religious fundamentalism - Lewis, Camille Kaminski (Studies in rhetoric and religion ;, 2007)
Romancing the Difference examines the rhetoric of fundamentalism as seen through the lens of Bob Jones University. Highlighting the romantic language used by religious separatists, Lewis argues that fundamentalism is not the angry cry of an outsider, nor is it the mocking of secular culture. Instead, it is an attempt to embody and articulate things that are lovely in order to woo others to an entirely different kind of life.